Gallium(III) Complex with Cloxyquin Ligands Induces Ferroptosis in Cancer Cells and Is a Potent Agent against Both Differentiated and Tumorigenic Cancer Stem Rhabdomyosarcoma Cells - Monika Hreusova; Vojtech Novohradsky; Lenka Markova; Hana Kostrhunova; Ivan Potočňák; Viktor Brabec; Jana Kasparkova (Bioinorganic Chemistry and Applications)
In this work, gallium(III) complex with cloxyquin (5-chloro-8-quinolinol, HClQ) ligands is shown to effectively inhibit proliferation of rhabdomyosarcoma cells, the frequent, aggressive, and poorly treatable cancer of children. It offers striking selectivity to cancer cells compared to noncancerous human fibroblasts. The data reveal that the complex induces ferroptosis in rhabdomyosarcoma cells, likely due to interfering with iron metabolism. Importantly, it can kill both bulk and stem rhabdomyosarcoma cells. To the best of our knowledge, this is the first compound based on metal other than Fe capable of inducing ferroptosis in cancer cells.